Exploring the Complex Relationship between Railroad Infrastructure, Operating Constraints, Maximum Speeds, and Public Schedules. Issue 8 (December 2018) - Lu, Alex; Kozlowski, Janek; Fahey, Sean; Whitman, Shaun
Outside the railroad industry, passenger trip times are often treated as a performance measure or yardstick of the industry's health. However, many factors not known or well understood by casual observers affect trip times—indeed, some are recognized techniques utilized by infrastructure owners to deliver journey time reductions. Factors triggering running time modifications include: track (design, maintenance, layout); infrastructure (structures, signal, power, grade crossings); cant deficiency, tractive effort, braking rates; rules, operating practices, timetable speeds; and schedulers' decisions on train performance modeling, en-route adjustments, and dwell times. Historical operating documents issued by railroads can be used to reconstruct events associated with trip timing changes, but their ephemeral nature makes it difficult. Because some information is never written down, the rationale for certain modifications may be unknowable. Public timetables offer a general sense of trends in service offerings but don't show what was really happening. Opposing industry trends can actually give rise to similar schedule impacts, e.g. deferred maintenance and track rehabilitation both lead to longer journey times. Applying forensic analysis methodology to Penn Central's Mohawk/Buffalo Divisions revealed that some time degradations are correlated to downgraded infrastructure and vehicle issues, but long-term changes were balanced. Metro-North's New Haven Line case study reveals how new stations, necessary safety modifications, increasing congestion, and temporary construction delays all contributed to recent timing changes. To maximize system performance, operators must balance time, capacity, and reliability subject to an overarching constraint of safe operations.